A court of thorns and roses - Maas, Sarah J. (2015)
"Dragged to a treacherous magical land she only knows about from stories, Feyre discovers that her captor is not an animal, but Tamlin, a High Lord of the faeries. As her feelings toward him transform from hostility to a firey passion, the threats against the faerie lands grow. Feyre must fight to break an ancient curse, or she will lose Tamlin forever"--
Keywords: Fantasy; Fairies -- Fiction; Blessing and cursing -- Fiction; Love stories; Electronic books